The cGMP system in normal and degenerating mouse neuroretina: New proteins with cGMP interaction potential identified by a proteomics approach. Issue 6 (5th December 2020) - Rasmussen, Michel; Welinder, Charlotte; Schwede, Frank; Ekström, Per
Abstract: The hereditary disease Retinitis pigmentosa results in severe vision loss due to photoreceptor degeneration by unclear mechanisms. In several disease models, the second messenger cGMP accumulates in the degenerating photoreceptors, where it may over‐activate specific cGMP‐interacting proteins, like cGMP‐dependent protein kinase. Moreover, interventions that counteract the activity of these proteins lead to reduced photoreceptor cell death. Yet there is little or no information whether other than such regular cGMP‐interactors are present in the retina, which we, therefore, investigated in wild‐type and retinal degeneration ( rd1, rd10, and rd2 ) mouse models. An affinity chromatography based proteomics approach that utilized immobilized cGMP analogs was applied to enrich and select for regular and potentially new cGMP‐interacting proteins as identified by mass spectrometry. This approach revealed 12 regular and 10 potentially new retinal cGMP‐interacting proteins (e.g., EPAC2 and CaMKII α ). Several of the latter were found to be expressed in the photoreceptors and to have proximity to cGMP and may thus be of interest when defining prospective therapeutic targets or biomarkers for retinal degeneration. Abstract : The involvement of cGMP (cyclic guanosyl monophosphate) in the retinal degeneration mechanism(s) is elusive, so we applied a proteomics approach to look for cGMP‐binding proteins in healthy and degenerating retinas. This approach revealed known binding proteins (PKG, PKAs, and PDEs) as well as potential new cGMP‐interacting proteins (EPAC2 (RAPGEF4), p‐CaMKIIα, p‐GSK3β, and MAPK1/3). The potential new cGMP‐interacting proteins showed proximity with cGMP in situ in the retina. While an indirect or direct binding of cGMP to these proteins is not yet verified, the results indicate them as important proteins to decipher the cGMP signaling pathway and hence the degeneration mechanisms. Illustration created with https://biorender.com/ .